Immigration and preferences for redistribution in Latin America - Martínez Correa, Julián (2019)
This paper analyzes the effect of immigration on preferences for redistribution in Latin America using harmonized censuses (IPUMS International) matched with LAPOP surveys for the 2008-2016 period. Our results suggest a negative relationship between the share of immigrants at the provincial level and the support for redistribution policies. These results are robust to different ways of measuring preferences for redistribution. This anti-redistribution effect is larger among those who consider themselves ideologically right-wing and among high-skilled and high-income individuals. Moreover, when considering immigrants' characteristics, we find that the anti-redistribution effect is fully explained by low-skilled immigration.